Avoidance and Delay of Medical Care in the Young: An Interdisciplinary Mixed-methods Study. (November 2018) - Montagni, Ilaria; Langlois, Emmanuel; Koman, Jason; Petropoulos, Margaux; Tzourio, Christophe
Prompt and appropriate health-seeking behaviour among young people is a public health priority worldwide. However, data indicate that non-health-seeking behaviour is common among young adults who are particularly likely to avoid and delay medical care. Our study investigates this phenomenon through an interdisciplinary mixed-methods approach. Quantitative and qualitative data are presented from university students from 11 higher education institutions in the city of Bordeaux, France, for a total of 16 individual interviews and a questionnaire survey of 126 students. Results show that main reasons for non-health-seeking behaviour among students are: time constraints, lack of information on available health services and economic problems. The transitional period of university studies is a further justification of students' difficulty in managing their medical care. Providing a clear picture of avoidance and delay of medical care (ADMC) and attached reasons was intended to explore strategies for promoting health-seeking behaviour in university students.